THE ROLE OF SELF-ESTEEM, PSYCHOLOGICAL WELL - BEING, EMOTIONAL SELF - EFFICACY, AND AFFECT BALANCE ON HAPPINESS: A PATH MODEL - Tayfun Dogan; Tarık Totan; Fatma Sapmaz (European Scientific Journal, ESJ, 2013)
﻿﻿The objective of this study is to examine the effects of self-esteem, psychological well-being, emotional self-efficacy and affect balance variables on happiness. The participants of the study are 340 (female n= 213; male n= 109) university students from Turkey. Oxford Happiness Questionnaire-Short Form, Self-Liking/Self-Competence Scale, Flourishing Scale, Emotional Self-efficacy Scale, and Positive-Negative Events Scale were used as data acquisition tools in the study. The relationships between the variables were examined via path analysis. According to the analysis it was determined that there are positive and significant relationship between psychological well-being, emotional self-efficacy and affect balance; and that psychological well-being and affect balance have positive effects on self-esteem and happiness, emotional self-efficacy has a positive effect on self-esteem and that self-esteem has a positive effect on happiness (χ2= 1.84, df= 1, χ2/df= 1.8, GFI= .99, CFI= .99, NFI= .99, RFI= .95, IFI= .99, TLI= .98, RMSEA= .05). In addition, it was concluded that 46% of the total variance regarding self-esteem is explained by psychological well-being, emotional self-efficacy and affect balance. It was also concluded that psychological well-being, emotional self-efficacy, affect balance and self-esteem explain 51% of the total variance regarding happiness.